2002
DOI: 10.1063/1.1486441
|View full text |Cite
|
Sign up to set email alerts
|

Atom-radical reaction dynamics of O(3P)+C3H5→C3H4+OH: Nascent rovibrational state distributions of product OH

Abstract: The reaction dynamics of ground-state atomic oxygen ͓O( 3 P)͔ with allyl radicals (C 3 H 5 ) has been investigated by applying a combination of crossed beams and laser induced fluorescence techniques. The reactants O( 3 P) and C 3 H 5 were produced by the photodissociation of NO 2 and the supersonic flash pyrolysis of precursor allyl iodide, respectively. A new exothermic channel of O( 3 P) ϩC 3 H 5 →C 3 H 4 ϩOH was observed and the nascent internal state distributions of the product OH (X 2 ⌸:Љϭ0,1) showed su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 62 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Experimental Studies: The lab-made crossed-beam apparatus for investigating gas-phase reaction dynamics has been described in detail elsewhere. [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] It consists of two radical-source chambers, each pumped by a 6-inch (1400 L s À1 ) baffled diffusion pump, and a scattering chamber, pumped by a 10-inch (3000 L s À1 ) baffled diffusion pump. The average base pressure in the scattering chamber was kept below 2.0 10 À6 Torr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental Studies: The lab-made crossed-beam apparatus for investigating gas-phase reaction dynamics has been described in detail elsewhere. [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] It consists of two radical-source chambers, each pumped by a 6-inch (1400 L s À1 ) baffled diffusion pump, and a scattering chamber, pumped by a 10-inch (3000 L s À1 ) baffled diffusion pump. The average base pressure in the scattering chamber was kept below 2.0 10 À6 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were reported in investigations of H-atom abstraction during reactions of O( 3 P) with ethyl and tert-butyl radicals, where the absence of activation barriers was also attributed to small CÀH BDEs (36.2 and 35.5 kcal mol À1 , respectively) and high exothermicities (DH = À67.3 and À67.2 kcal mol À1 , respectively). [7,13,16] Note that for the main reaction (1), H-atom abstraction from the central C(2)ÀH bond was not considered, since unfavourable endothermic reactions were predicted to lead to OH + 1 C(CH 3 ) 2 and OH + 3 C(CH 3 ) 2 (DH = 1.6 and 3.5 kcal mol À1 , respectively).…”
Section: Ab Initio Reaction Pathways: Addition Versus Abstractionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] The complexity of the competition between bond fission and isomerization pathways is surprising for such a small system, composed of only four heavy atoms and five hydrogen atoms. Previous studies have sought to probe the product branching and dynamics of this reaction.…”
Section: Primary Photodissociation Pathways Of Epichlorohydrin and Anmentioning
confidence: 99%
“…Choi and co-workers [4][5][6] studied the reaction of O( 3 P) with the allyl radical using CBS-Q and CBS-QB3 levels of theory. Raman et al [7] created the CH 2 CCH 2 OH intermediate photolytically, and observed bimolecular products; they used G3//B3LYP electronic structure calculations to rationalize their findings.…”
Section: Introductionmentioning
confidence: 99%